IMPLEMENTATION OF THE STORYTELLING METHOD IN ISLAMIC RELIGIOUS EDUCATION LEARNING IN SENIOR HIGH SCHOOL - Amnur Muhammad Ariya Nugroho; Meriyati Meriyati; Fitriani Fitriani (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2026)
This study examines the implementation of the storytelling method in Islamic Religious Education instruction at the high school level as an approach that creates a more lively, interactive, and meaningful learning environment. Through the presentation of meaningful stories, students not only understand religious concepts cognitively but also experience their significance emotionally and affectively. The research approach used is descriptive qualitative, employing data collection techniques such as observation, interviews, and documentation. This study was conducted at SMA Negeri 2 Gadingrejo with 2 PAI teachers and 64 eleventh-grade students as participants. The results of the study indicate that the storytelling method is effective in increasing students’ interest in learning, deepening their understanding of Islamic values, and fostering religious character in students’ daily lives. Additionally, the interaction between teachers and students became closer and more open, creating an inclusive learning environment and fostering emotional closeness. However, there were several challenges, such as limited class time and teachers’ ability to develop and deliver stories relevant to the students’ life contexts. Overall, the use of the storytelling method contributed positively to the creation of an inspiring, reflective, and character-focused Islamic Education learning process. This method also supports a contextual learning approach by linking the curriculum to students’ real-life experiences, so that religious values can be applied in practical ways in their daily lives.